Hyaluronic acid fillers safeguarding women's health - Mekan R. Orazov; Viktor E. Radzinskii; Evgenii D. Dolgov (LLC "MEDIAFORMAT", 2023)
Today, pelvic floor dysfunction (PFD) is one of the most pressing issues of modern gynecology. In patients with no macroscopic defects of the pelvic floor myofascial compartment, vaginal relaxation syndrome (VRS) that is highly prevalent among sexually active patients of child-bearing age represents the major PFD phenotype. Pregnancy and vaginal delivery constitute one of the most important etiological factors of VRS deter-mining high prevalence of the disorder. Furthermore, PFD results from the age-induced hypoestrogenism observed in peri- and postmenopausal patients. In such cases VRS and gaping vaginal opening may occur as early precursors of PFD. Based on the foregoing, it is important to consider the intimate contouring surgery as one of the most accessible and effective VRS correction methods for pelvic health restoration, improvement of the quality of life in general and sexual function in particular.